Cell Therapy for Parkinson's Disease: A Translational Approach to Assess the Role of Local and Systemic Immunosuppression. Issue 7 (3rd March 2016) - Aron Badin, R.; Vadori, M.; Vanhove, B.; Nerriere‐Daguin, V.; Naveilhan, P.; Neveu, I.; Jan, C.; Lévèque, X.; Venturi, E.; Mermillod, P.; Van Camp, N.; Dollé, F.; et al.
Abstract : Neural transplantation is a promising therapeutic approach for neurodegenerative diseases; however, many patients receiving intracerebral fetal allografts exhibit signs of immunization to donor antigens that could compromise the graft. In this context, we intracerebrally transplanted mesencephalic pig xenografts into primates to identify a suitable strategy to enable long‐term cell survival, maturation, and differentiation. Parkinsonian primates received WT or CTLA4‐Ig transgenic porcine xenografts and different durations of peripheral immunosuppression to test whether systemic plus graft‐mediated local immunosuppression might avoid rejection. A striking recovery of spontaneous locomotion was observed in primates receiving systemic plus local immunosuppression for 6 mo. Recovery was associated with restoration of dopaminergic activity detected both by positron emission tomography imaging and histological examination. Local infiltration by T cells and CD80/86+ microglial cells expressing indoleamine 2, 3‐dioxigenase were observed only in CTLA4‐Ig recipients. Results suggest that in this primate neurotransplantation model, peripheral immunosuppression is indispensable to achieve the long‐term survival of porcine neuronal xenografts that is required to study the beneficial immunomodulatory effect of local blockade of T cell costimulation. Abstract : The intragraft expression of CTLA4‐Ig, a costimulation blocker, and the duration of the peripheral immunosuppressive treatment can improve cell survival and delay local xenogeneic T cell activation following intracerebral transplantation of transgenic CTLA4‐Ig+/+ pig xenografts in parkinsonian nonhuman primates.